DOI: 10.31274/rtd-180813-16229
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of Iowa's automated red light running enforcement programs

Abstract: One of the most controversial topics facing traffic engineers, city councils, and public awareness groups is the implementation of automated red light running enforcement camera systems at signalized urban intersections. Red light running is a significant safety problem as drivers become more aggressive on roads, and become impatient waiting for a traffic signal to change. Red light running camera systems are automated Month Revenue Service Charge

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…Results indicated that 25 times more RLR violations occurred at approaches with no enforcement than where RLR cameras were in place. A complete discussion of results for Council Bluffs and Clive is presented in the project report (17 ).…”
Section: Rlr Camera Enforcement In Iowamentioning
confidence: 99%
“…Results indicated that 25 times more RLR violations occurred at approaches with no enforcement than where RLR cameras were in place. A complete discussion of results for Council Bluffs and Clive is presented in the project report (17 ).…”
Section: Rlr Camera Enforcement In Iowamentioning
confidence: 99%
“…According to the Ruby and Hobeika [20], the installation of these systems reduced the red light violation cases to 0.17 to 7 vehicles per 10.000 cars from 2 to 11 vehicles. Fitzsimmons et al [9] investigated the effects of these systems on the number of accidents that occurred at intersections. From the analyzes it was concluded that the total number of accidents at intersections was reduced by 44%, the rear-front collisions were reduced by 40% and non rear-front collisions were reduced by 90%.…”
Section: Number Of Accidents At Intersections (%)mentioning
confidence: 99%
“…The When Table 1 is examined, it can be seen that the ratios of the traffic accidents at intersections have a fixed value over years and no significant decrease was observed. Many studies carried out around the world also indicated that the drivers are not disciplined in utilizing the lanes and speedy driving, red light violations were among the important problems affecting the traffic safety and increasing the road accidents [2,[8][9][10]. In their study, Coruh et al [2]found that the fast rate of urbanization, along with increasing employment rates, places significant strain on have an important effect on traffic accidents for Turkey.…”
Section: Yearmentioning
confidence: 99%
“…Installation of this system in 254 UK cities resulted the reduction of fatal and injury accidents by 18% (Traffic Technology Today 2009). The study in the United States has determined that after installation of this system the number of accidents at the intersections has decreased by 44% (Fitzsimmons et al 2007).…”
Section: Intelligent Transport Systems As Traffic Safety Measurementioning
confidence: 99%